Ausgespäht und überwacht, erschreckend wunderbar geschaffen: Gott und Mensch in Psalm 139 - Köckert, Matthias (Zeitschrift für Theologie und Kirche, 2010)
In the early Hellenistic period, the author of Ps 139 articulates for the first time the insight that God has known him in his individuality from the beginning of the world. This insight changes his attitude to God fundamentally from verses 1–6 through verses 7–18 and then to verses 19–24.